The biology of Epidermal Growth Factor Receptor (EGFR) from regulating cell cycle to promoting carcinogenesis: the state of art including treatment options - Patrizia Viola (Annals of Cytology and Pathology - Peertechz Publications, 2020)
The current definition of cancer is the creation of atypical cells capable to rapidly grow beyond the normal boundaries and spread to distant organs. To do so tumour cells have to acquire to the ability to proliferate continuously and avoid apoptosis. An important role in this process is played by growth factors and their receptors. Amongst many, one of the most important interaction is between the Epidermal growth factor (EGF) and its receptor (EGFR) which are frequently mutated or upregulated in human cancers particularly in non-small cell carcinoma of the lung (NSCLC). The biding leads to protein activation, cell proliferation and decreased apoptosis. However, in this subset of tumours, the blockage of this interaction by EGFR-targeting drugs has shown an overall outcome improvement leading to the era of target therapy. The result is that patients are now routinely screened for a series of actionable mutations to be given the best possible therapy available for their specific type of tumour limiting the side effect of broad-spectrum chemotherapy. This paper will review the biology of EGFR receptor, the type and role of its mutation and the clinical implication for patients with NSCLC harbouring these mutations.